Enhanced Flavonoid Accumulation Reduces Combined Salt and Heat Stress Through Regulation of Transcriptional and Hormonal Mechanisms - Jan, Rahmatullah; Kim, Nari; Lee, Seo-Ho; Khan, Muhammad Aaqil; Asaf, Sajjad; Lubna,; Park, Jae-Ryoung; Asif, Saleem; Lee, In-Jung; Kim, Kyung-Min (Frontiers in Plant Science, 2021)
Abiotic stresses, such as salt and heat stress, coexist in some regions of the world and can have a significant impact on agricultural plant biomass and production. Rice is a valuable crop that is susceptible to salt and high temperatures. Here, we studied the role of flavanol 3-hydroxylase in response to combined salt and heat stress with the aim of better understanding the defensive mechanism of rice. We found that, compared with wild-type plants, the growth and development of transgenic plants were improved due to higher biosynthesis of kaempferol and quercetin. Furthermore, we observed that oxidative stress was decreased in transgenic plants compared with that in wild-type plants due to the reactive oxygen species scavenging activity of kaempferol and quercetin as well as the modulation of glutathione peroxidase and lipid peroxidase activity. The expression of high-affinity potassium transporter (HKT) and salt overly sensitive (SOS) genes was significantly increased in transgenic plants compared with in control plants after 12 and 24 h, whereas sodium-hydrogen exchanger (NHX) gene expression was significantly reduced in transgenic plants compared with in control plants. The expression of heat stress transcription factors (HSFs) and heat shock proteins (HSPs) in the transgenic line increased significantly after 6 and 12 h, although our understanding of the mechanisms by which the F3H gene regulates HKT, SOS, NHX, HSF, and HSP genes is limited. In addition, transgenic plants showed higher levels of abscisic acid (ABA) and lower levels of salicylic acid (SA) than were found in control plants. However, antagonistic cross talk was identified between these hormones when the duration of stress increased; SA accumulation increased, whereas ABA levels decreased. Although transgenic lines showed significantly increased Na+ ion accumulation, K+ ion accumulation was similar in transgenic and control plants, suggesting that increased flavonoid accumulation is crucial for balancing Na+/K+ ions. Overall, this study suggests that flavonoid accumulation increases the tolerance of rice plants to combined salt and heat stress by regulating physiological, biochemical, and molecular mechanisms.